ENT 530 Social Media Portfolio: NIMSchoco by Fitri / Muhammad Fitri Mazilan - Mazilan, Muhammad Fitri (2021)
By doing this individual assignment, I will learn how it is to build an online business from the scratch to the end. The platform that I was instructed to use for this assignment is Facebook (FB). I love the idea of using Facebook as a medium of doing business as it is the biggest social media platform as for today. This means that many people will either purposely or coincidentally find out about the business as many people are using the social media. This assignment also will teach us how to stay afloat during this pandemic as we are not able to go out and restricted from doing a physical business as it might spread and worsen the Covid-19 cases. I am choosing NIMSchoco as my business product and sold it to the Facebook as my business platform. This is because I have tried the product myself before and it was so good in my opinion. I also have done quite good amount of research about this product and many customers all over Malaysia has given good reviews on this product thus I decided to choose this product as my business product for this assignment. NIMSchoco is a type of chocolate snack that went viral these days in Malaysia and Malaysians usually called it as ‘chocojar’. I have tried a lot of brands of this snack since it went viral and from my standpoint, NIMSchoco has the best version of the snack. The chocolate drippings are all over the jar and NIMSchoco product also do not emit such ‘fishy’ smell as the other brands would. By doing this individual assignment, I would learn a lot about handling an online business, also on how or what should I do in order to maximize our profit and eliminate problems if I am destined to be an entrepreneur in the future.